2020
DOI: 10.1155/2020/2495157
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals Novel Specific Metastatic Mutations in Chinese Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) accounts for more than 75% of renal cell carcinoma. Nearly 25% of ccRCC patients were diagnosed with metastasis. Though the genomic profile of ccRCC has been widely studied, the difference between localized and metastatic ccRCC was not clarified. Primary tumor samples and matched whole blood were collected from 106 sporadic patients diagnosed with renal clear cell carcinoma at Qilu Hospital of Shandong University from January 2017 to November 2019, and 17 of them were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…A genomic study sequenced 106 clear cell RCCs and found no altered PBRM1 in the metastatic group and a relatively high frequency of BAP1 (24% vs 10%) between the metastatic and non-metastatic groups. 20 Other studies have shown that mutated BAP1 , but not PBRM1 , correlates with decreased survival in clear cell RCC. 1 A model for clear cell RCC development proposed that the PBRM1 mutation results in low-grade clear cell RCC, whereas the BAP1 mutation results in high-grade clear cell RCC.…”
Section: Discussionmentioning
confidence: 97%
“…A genomic study sequenced 106 clear cell RCCs and found no altered PBRM1 in the metastatic group and a relatively high frequency of BAP1 (24% vs 10%) between the metastatic and non-metastatic groups. 20 Other studies have shown that mutated BAP1 , but not PBRM1 , correlates with decreased survival in clear cell RCC. 1 A model for clear cell RCC development proposed that the PBRM1 mutation results in low-grade clear cell RCC, whereas the BAP1 mutation results in high-grade clear cell RCC.…”
Section: Discussionmentioning
confidence: 97%
“…To sum up, the two genes may not be lung cancer specific susceptible genes, and the association of their P/LP variants and cancer risk warrants further investigation. In terms of the other two significant variants in the case–control analysis (FDR < 0.05), germline BRIP p.L340F variant was detected in breast cancer patients [ 71 ] and MUTYH p.R19* variant was detected in patients with colorectal cancer [ 72 ], clear cell renal cell carcinoma [ 73 ], and breast cancer [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of TEK has been noted in aggressive ccRCC for years (41). Recently, when compared gene prevalence between nonmetastatic and metastatic ccRCC by target next generation sequencing from 106 sporadic cases, higher frequencies of TEK mutations involved in metastatic cohort (42). Since Tie2 signaling influences vascular permeability, low expression of Tie2 may potentiate inflammatory cells migration into tumor microenvironment (43).…”
Section: Discussionmentioning
confidence: 99%